Subglosso-palatal membrane a rare cause of neonatal respiratory distress: A case report - Vaibhav Pandey (Journal of Indian Association of Pediatric Surgeons, 2014)
Subglosso-palatal membrane is a rare cause of acute respiratory distress in newborn. Contrary to the earlier reported cases in which immediate splitting or excision of membrane has been described as measure to relief respiratory distress, we managed our case successfully without any emergency surgical procedure.